1997
DOI: 10.1097/00004836-199706000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Autonomic Nerve Tumor with Giant Abscess

Abstract: We report a gastrointestinal autonomic nerve tumor of the stomach with a giant abscess. The patient had fever and pain and was found to have anemia and an abdominal mass. X-ray and endoscopic examination showed a gastric submucosal tumor with a fistula to the gastric lumen. Partial gastrectomy was performed and no metastasis was found. On gross examination, the excised tumor was seen to be a submucosal solid tumor with a giant abscess. Alpha streptococci and anaerobic gram-negative rods were cultured from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Cases of GISTs involving the stomach presenting as an intra-abdominal abscess are extremely rare, and only 7 cases have been reported in the English literature (table 1 ) [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. In some cases with GISTs, tumor degeneration or necrosis can result in bleeding into the gastrointestinal lumen or peritoneum space, and bleeding into the intra-abdominal space can cause an intra-abdominal abscess.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of GISTs involving the stomach presenting as an intra-abdominal abscess are extremely rare, and only 7 cases have been reported in the English literature (table 1 ) [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. In some cases with GISTs, tumor degeneration or necrosis can result in bleeding into the gastrointestinal lumen or peritoneum space, and bleeding into the intra-abdominal space can cause an intra-abdominal abscess.…”
Section: Discussionmentioning
confidence: 99%
“…GANTs are found in all regions of the small intestine, stomach, and less commonly in mesentery, peritoneum, omentum and esophagus (4–8). Almost all reports mention that primary localization of GANT in childhood is stomach (6,7,9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Histopathologic examination showed that the neoplastic cells consisted of spindle cells with increased mitotic activity. It is well‐known that immunocytochemical and ultrastructural examination is essential in distinguishing GANT from gastrointestinal stromal tumor, and the presence of neuronal differentiation with the absence of myogenic, schwann and epithelial features are required for diagnosis (2,5,8). The immunocytochemical test results of our case (positivity for NSE and S‐100 protein, negativity for cytokeratin, desmin, and actin) confirmed diagnosis of GANT.…”
Section: Discussionmentioning
confidence: 99%